PERAN RETICULOCYTE HEMOGLOBIN EQUIVALENT (Ret-He) UNTUK SKRINING DEFISIENSI BESI PADA ANAK USIA 6 BULAN-5 TAHUN - , Ester Tri Rahayu ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Anemia is a global health problem, as the main cause of anemia is iron deficiency so that the prevalence of anemia is often used to describe the prevalence of iron deficiency anemia. Based on WHO data, the prevalence of anemia in pre-school age (0 to 4.99) in Indonesia including weight category (>40%) and household-based health survey in Indonesia, the prevalence in preschool children is 47%. In infants and early childhood, iron deficiency associated with delays and disorder both motor and intellectual development that may be irreversible, so an early detection is needed. There are three stages of iron deficiency. Gold standard for the examination of iron deficiency is iron staining of bone marrow with Prussian Blue but very invasive so indirect tests with hematological and biochemical parameters is commonly used. Hematologic parameters can only detect advanced stages of deficiency, biochemical parameters required special preparation and influenced with inflammatory conditions. Flowcytometry technique development on the latest automated hematology instruments can estimate the hemoglobin content of reticulocytes (Reticulocyte Hemoglobin Equivalent / RET-He) in order to describe the actual condition of erythropoiesis and iron deficiency can be detected at an early stage. The aims of this study are to determine the diagnostic performance of Ret-He in screening of iron deficiency in children aged 6 months to 5 years. This study is a cross sectional study to determine the diagnostic performance of Ret-He. The subjects of this study were 94 healthy children aged 6 months-5 years taken from Posyandu in Yogyakarta district and has obtained the consent of their parent/guardian. Ret-He examination using flowcytometry method by Sysmex XT-2000i Hematology Analyzer. Ferritin examination using electrochemiluminescens methods with Elecsys 1010. At the cut-off Ret-He 28 pg resulted in a sensitivity, specificity, PPV, NPV, LR +, and LR-respectively 81.3%, 93.6%, 72%, 96%, 12.7 and 0,2. High specificity, sensitivity and LR + values is more suitable for diagnostic purposes. At the cut-off Ret-He 29.5 pg the sensitivity, specificity, PPV, NPV, LR +, and LR- 93.8%, 71.8%, 41%, 98%, 3.33 and 0.086. The results were very high sensitivity with sufficient specificity, high NPV and LR- which resulted in major changes to the post-test probability indicates the value of RET-He in this cut-off is suitable for screening purposes iron deficiency in children aged 6 months to 5 years.